Waste seashell as calcium oxide catalyst for bio-oil production from empty fruit bunch - Nurfatirah Nordin (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2017)
The general objective of this research is to evaluate the catalytic pyrolysis of empty fruit bunch (EFB) with waste seashell in fixed bed reactor towards the distribution of product yields and composition of bio-oil obtained via non-catalytic and catalytic pyrolysis process. The specific objectives are as follows to optimize the effect of pyrolysis parameters of EFB such as pyrolysis temperature, particle size and nitrogen flow rate by central composite design (CCD) in fixed bed reactor; to characterize the catalyst CaO from waste seashell and the pyrolysed bio-oil; to evaluate the effect of waste seashell catalyst in the pyrolysis process.